Faster turnover of new soil carbon inputs under increased atmospheric CO2. (2nd June 2017) - van Groenigen, Kees Jan; Osenberg, Craig W.; Terrer, César; Carrillo, Yolima; Dijkstra, Feike A.; Heath, James; Nie, Ming; Pendall, Elise; Phillips, Richard P.; Hungate, Bruce A.
Abstract: Rising levels of atmospheric CO2 frequently stimulate plant inputs to soil, but the consequences of these changes for soil carbon (C) dynamics are poorly understood. Plant‐derived inputs can accumulate in the soil and become part of the soil C pool ("new soil C"), or accelerate losses of pre‐existing ("old") soil C. The dynamics of the new and old pools will likely differ and alter the long‐term fate of soil C, but these separate pools, which can be distinguished through isotopic labeling, have not been considered in past syntheses. Using meta‐analysis, we found that while elevated CO2 (ranging from 550 to 800 parts per million by volume) stimulates the accumulation of new soil C in the short term (<1 year), these effects do not persist in the longer term (1–4 years). Elevated CO2 does not affect the decomposition or the size of the old soil C pool over either temporal scale. Our results are inconsistent with predictions of conventional soil C models and suggest that elevated CO2 might increase turnover rates of new soil C. Because increased turnover rates of new soil C limit the potential for additional soil C sequestration, the capacity of land ecosystems to slow the rise in atmospheric CO2 concentrations may be smaller than previously assumed. Abstract : We present a meta‐analysis on the effect of rising CO2 on new and old soil carbon stocks, synthesizing data from CO2 enrichment studies in which isotopic labeling allowed to distinguish between these two carbon pools. We found that in longer‐term experiments (1‐4 years), elevated CO2 does not increase the amount of new soil C, even though plant growth data indicate that soil C input is higher than under ambient conditions. Together, these findings suggest that new C decomposes faster under elevated CO2 .